2(2x+3)-15x=2x-7

Simple and best practice solution for 2(2x+3)-15x=2x-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(2x+3)-15x=2x-7 equation:



2(2x+3)-15x=2x-7
We move all terms to the left:
2(2x+3)-15x-(2x-7)=0
We add all the numbers together, and all the variables
-15x+2(2x+3)-(2x-7)=0
We multiply parentheses
-15x+4x-(2x-7)+6=0
We get rid of parentheses
-15x+4x-2x+7+6=0
We add all the numbers together, and all the variables
-13x+13=0
We move all terms containing x to the left, all other terms to the right
-13x=-13
x=-13/-13
x=1

See similar equations:

| (t+7)=32 | | 5x-5.52=-4.32 | | m=4m+9 | | 0.5/x=20 | | -5(3x-7)+11=x | | 6w=45-4w | | 2^x+7=5/4 | | 3/2x-5=2/x-4 | | 3x-5.42=-3.89 | | -4(2+x)=56 | | 2(6z+)=28 | | 2x-12=6x+24 | | 2x+8-7x-2=3x+14 | | 3(4-x)=-27 | | -2+3x=6x+4 | | 6x–11=7 | | 3k^2-13k+10=0 | | 6x–11=7 | | x^2=2.89^3 | | X+6=2-2x | | 3k^2-13k+-10=0 | | −4(2+x)=56 | | (9x+7)+(-3x+20)=39 | | H(x+2)=(x+2)^2-2(x+2) | | 5a+2​ =a | | m÷3.5=16 | | –2x=–18 | | 1=w/2+7 | | -8(x+9)+2=7x-27 | | 575=23(x+16) | | 3(5x+5)=-39+9 | | 1/4/x=0 |

Equations solver categories